O relacionamento corporativo na web norteado pelo gerenciamento da impressão organizacional - Sandini, Silvana Maria (2016)
The study aims to build a matrix to develop the corporate relationship with target groups on the Web, based on the Organizational Impression Management. Therefore, methodological procedures are adopted and inspired in Depth Hermeneutics (Thompson, 2002) that, enhanced by Content Analysis (Bardin, 2009 [1977]), enables scanning the Locaweb company channels, to analyze, interpret and validate the formatting of a suitable matrix to the specific characteristics of cyberspace. During the research are discussed concepts such as social changes in the corporate scenery, identity, image, reputation, corporate relationship, social networks, social media, virtual territories of organizations, Organizational Impression Management and Communication Firewall. Thus, it is observed that, if aware of the complexity of all the exposed elements in the array, the Organizational Impression Management can be arranged in a systemic way and guide the positioning of spectacular organizations on the Web, in order to achieve greater compliance and support of public at a time of significant changes that directly impact the organizationpublic relationship.